Formulasi dan Uji Aktivitas Antibakteri Sabun Cair Ekstrak Daun Jeruk Purut (Citus hystrix) terhadap Bakteri Staphylococcus aureus ATCC 25923 dan Escherichia coli ATCC 25922 - Iqbal Sirajudin Maulidinawan; Tatiana Siska Wardani; Bagas Ardiyantoro (Pusat riset dan Inovasi Nasional, 2025)
Skin that is prone to bacterial infections requires proper care using products containing antibacterial agents. One potential alternative is kaffir lime leaves (Citrus hystrix), which are known to contain antibacterial compounds. This study aimed to evaluate the formulation of liquid soap containing kaffir lime leaf extract and to determine the optimal concentration for inhibiting bacterial growth. An experimental laboratory design was applied, and the antibacterial effectiveness was tested using the disk diffusion method against two test bacteria, namely Staphylococcus aureus and Escherichia coli. Statistical analysis was performed using One-Way ANOVA, followed by Scheffe’s post-hoc test to identify significant differences among treatment groups. The results indicated that the liquid soap containing kaffir lime leaf extract exhibited good physical quality and met standard parameters, including organoleptic evaluation, pH, viscosity, and foam height tests. Antibacterial testing showed that the highest inhibition zone against Staphylococcus aureus was observed at a 15% concentration with a zone diameter of 18.28 mm (strong category), while the highest inhibition zone against Escherichia coli was also at a 15% concentration with a diameter of 19.03 mm (strong category). The One-Way ANOVA results showed a significance value (p < 0.05), indicating a statistically significant difference among treatments for both bacterial species. These findings suggest that liquid soap formulated with kaffir lime leaf extract, particularly at a 15% concentration, has strong antibacterial activity and potential as an effective skin care product. Further studies are recommended to evaluate safety, stability, and long-term effectiveness.